Users’ Perceptions Towards the E-Payment System in Kathmandu Metropolitan City - Adhikari, Rajaram (Journal of Durgalaxmi, 2024)
The main objective of this study was to analyze the users’ perception towards the use of electronic payment systems in Kathmandu Metropolitan City. Thespecific objectives were to examine the perception of users related to factors like availabilities, performance benefits, and security and trust association with the use of electronic payment systems. This research is designed descriptively. The sample size in this study was drawn from people residing in Kathmandu metropolitan city 16, Nayabazar, Kathmandu area in which most of the branches of banks were located and convenient for the researcher. Six bank branches with 40 users each were selected altogether 240 and the valid sample size was 220 legitimate responders (91.67% ). Convenience and quota sampling are two non-probability sampling techniques that are used to choose samples from the community. Users in the Kathmandu metropolitan area believed that the e-payment system's availability was adequate overall. Users found the locations of the ATMs to be handy. While users in the Kathmandu metropolitan area were dissatisfied with the availability and functionality of e-payment systems, they were pleased with the many advantages these systems offered. Further, service providers should focus on the responsive e-payment system in order to raise positive users’ perceptions. In the future, the researcher can gather information from supermarkets, shopping centers,and other locations in Nepal, as well as study the use of e-payment systems and their danger in relation to larger or lower volume transactions.